2013
DOI: 10.5694/mja12.11640
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the incidence of hospital‐acquired complications and their effect on length of stay using CHADx

Abstract: An automated CHADx reporting system can be used to collect data on patients with hospital-acquired complications. Such data can be used to increase emphasis on patient safety and quality of care and identify potential opportunities to reduce LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 17 publications
7
51
0
Order By: Relevance
“…Readmission rates, i.e., within 3 months post-discharge.Rate of surgical interventions during hospital stay.Incidence of clinical in-hospital complications according to the Classification of Hospital-Acquired Diagnoses (CHADx) [15]. The CHADx tool is a hierarchical classification of encoded diagnoses based on the International Classification of Diseases-10 (ICD-10), which allows quantification of the burden of in-hospital complications.…”
Section: Methodsmentioning
confidence: 99%
“…Readmission rates, i.e., within 3 months post-discharge.Rate of surgical interventions during hospital stay.Incidence of clinical in-hospital complications according to the Classification of Hospital-Acquired Diagnoses (CHADx) [15]. The CHADx tool is a hierarchical classification of encoded diagnoses based on the International Classification of Diseases-10 (ICD-10), which allows quantification of the burden of in-hospital complications.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies note the limitations of using administrative data, such as potential misclassification, lack of socio‐demographic information and the likely underreporting of diagnoses and procedures (Grosse, Boulet, Amendah, & Oyeku, ). Additionally, although CHADx outcomes have been used in several previous studies and found to be a reliable measure (Michel et al., ; Trentino, Swain, Burrows, Sprivulis, & Daly, ), their reliance on coded administrative data potentially exacerbates these issues and analyses should be viewed accordingly. In addition, other factors such as nurse staffing and skill mix, found in previous studies to be important predictors of patient outcomes (Duffield et al., ; Roche, Duffield, Aisbett, Diers, & Stasa, ), were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…CHADx outcomes have been used in several previous studies and found to be a reliable measure Trentino, Swain, Burrows, Sprivulis, & Daly, 2013), their reliance on coded administrative data potentially exacerbates these issues and analyses should be viewed accordingly. In addition, other factors such as nurse staffing and skill mix, found in previous studies to be important predictors of patient outcomes (Duffield et al, 2011;Roche, Duffield, Aisbett, Diers, & Stasa, 2012), were not measured.…”
Section: Limitationsmentioning
confidence: 99%
“…Another example of this bias is when researchers study the impact of an event during a hospital stay (eg, a hospital‐acquired infection) on length of stay. Many researchers simply compare the total lengths of stay for patients who did and did not experience an infection, but this includes the time before participants had an infection, which introduces immortal time bias 8 , 9 . Another way to understand this is to think that the longer one is in hospital, the greater the risk of developing infection — a chicken and egg problem.…”
Section: Extensions To Survival Analysismentioning
confidence: 99%
“…Many researchers simply compare the total lengths of stay for patients who did and did not experience an infection, but this includes the time before participants had an infection, which introduces immortal time bias. 8,9 Another way to understand this is to think that the longer one is in hospital, the greater the risk of developing infectiona chicken and egg problem. Including this immortal time in the study design means the effect of infection on length of stay is greatly exaggerated.…”
Section: Immortal Time Biasmentioning
confidence: 99%